Changes in the syndesmotic reduction after syndesmotic screw fixation for ankle malleolar fractures: One-year longitudinal evaluations using computer tomography. Issue 10 (October 2016) - Endo, Jun; Yamaguchi, Satoshi; Saito, Masahiko; Morikawa, Tsuguo; Akagi, Ryuichiro; Sasho, Takahisa
Abstract: Introduction: To evaluate time-dependent changes in the syndesmotic reduction after syndesmotic screw fixation and one year after screw removal for ankle malleolar fractures, and to assess whether the incidence of syndesmotic malreduction changes depending on the measurement method. Methods: We assessed twenty patients who underwent syndesmotic screw fixation for ankle fractures. The syndesmotic screws were removed after six weeks of the fracture surgery. Syndesmotic reduction was assessed within two weeks of the fracture surgery and one year after the screw removal using the axial computer tomographic images. Side-to-side differences in the anterior and posterior tibiofibular distances, anteroposterior fibular translation, and fibular rotation were measured. Results: The mean anterior tibiofibular distance was 0.7 mm after syndesmotic fixation. It increased to 1.9 mm at one year after screw removal ( p  = 0.002). After syndesmotic fixation, four ankles had malreduction of the anterior tibiofibular distance, including three ankles with widening and one with overtightening. At one year, eight ankles had malreduction, all of whom had widening. The other measurement values did not change over time (0.1 mm vs. 0.6 mm for the posterior tibiofibular distance, 0.2 mm vs. 0.3 mm for the anteroposterior fibular translation, and 0.7 ° vs. 0 ° for the fibular rotation). The incidences of malreduction were significantly different depending on the definition of malreduction, ranging from 10% to 50% after syndesmotic fixation ( p  = 0.01) and from 20% to 60% at one year after screw removal ( p  = 0.02). Conclusions: The anterior tibiofibular distance widened after one year of syndesmotic screw removal. The incidence of malreduction varied depending on the measurement method.